Brand essense: elements and added value - V. S. Nikitina (E-Management, 2021)
The emergence of branding as one of the areas of business has helped to draw the attention of management to the need to give a product or service an emotional reinforcement, a certain factor, working with the subconscious of the consumer. Scientists have experimentally found out that a person’s connection with a product is much stronger if it is based not only on conditionally rational judgments about it, but also on the sensory perception of the brand, the emotional attitude to the company that offers this product.This article is devoted to the study of the brand as the basis for the existence of the added value of the product, which brings the buyer additional satisfaction of certain needs, which may not even be directly related to the tasks potentially solved by the purchased product. In the course of writing the article, the author collected and structured the theorists ‘ ideas about the essence of the brand and its elements, which can be managed by a brand manager within the framework of working with the product. The paper considers the brand as one of the key factors influencing the final price of the product on the shelf, from the aspect of the real costs accompanying its construction, development and maintenance, as well as from the subjective benefits received by the consumer from contact with it. The author of the article provides examples of cases of real companies related to building a brand and its strong influence on the value that the final product carries.